Analisis dan Perancangan Sistem Basis Data Catatan Waktu Kerja dan Proyek Karyawan pada PT Rekayasa Engineering - Sutoyo, Rhio; Marpaung, Franky Hadinata (Bina Nusantara University, 2013)
The purpose of this research is to analyze and implement a system for recording employee working time and project time, leave request, overtime request, proposal submission, and paperwork revisions registration at PT Rekayasa Engineering. Collecting information is conducted by surveys to the company, interviews with several employees in the company, and examining documents and procedures used by PT Rekayasa Engineering. The database design is created using lifecycle methodology, namely: conceptual design, logical design, and physical design. The result of this research is a database system which is designed and can be used to process operational procedures of the company and to record the working time and project needed by the PT Rekayasa Engineering. Furthermore, this research also produces a prototype application that can be used as a working model for the system. Using the new database system and the application, information needed by the company is fulfilled. Thus, it allows the company to work more effectively and efficiently.